Data Security Issues In Cloud Computing: Review - Ahmed, Hussam Alddin Shihab; Mohamad Fadli, Zolkipli (Penerbit UMP, 2016)
Cloud computing is an internet based model that empower on demand ease of access and pay for the usage of each access to shared pool of networks. It is yet another innovation that fulfills a client's necessity for computing resources like systems, stockpiling, servers, administrations and applications. Securing the Data is considered one of the principle significant challenges and concerns for cloud computing. This persistent problem is getting more affective due to the changes in improving cloud computing technology. From the perspective of the Clients, cloud computing is a security hazard especially when it comes to assurance affirmation issues and data security, remain the most basically which backs off for appropriation of Cloud Computing administrations. This paper audits and breaks down the essential issue of cloud computing and depicts the information security and protection of privacy issues in cloud.